DIGITAL SECURITY IN EDUCATIONAL TRAINING PROGRAMS: A STUDY BASED ON FUTURE TEACHERS’ PERCEPTIONS - María José Latorre-Medina; Chaimae Tnibar-Harrus (Інформаційні технології і засоби навчання)
A key aspect of future teacher training in this highly digitalized period of education requires a specific focus on digital skills, especially in the area of security. This study delves into this issue by means of a quantitative, theoretical and systematic review of future teachers currently in training at the Faculty of Education, Economy and Technology of Ceuta of the University of Granada (Spain). The specific intention is to determine their perception of the instruction they receive on digital matters, concretely on cybersecurity during their phase of pre-service. To carry out the project, the study resorted to a descriptive method by submitting the participants to a specifically designed questionnaire entitled “Digital Security Competence Required for Teachers”. Examinations of the psychometric properties of the questionnaire reveal its relevance and reliability. The intention, after applying descriptive and inferential statistics tests, was to determine whether students in pre-service training really feel competent on digital matters or if they feel need more theoretical-practical training, especially in the area of security. The general findings reveal that future female teachers pursuing a university degree in Early Childhood Education, although competent from the techno-pedagogical viewpoint, indicate that attaining a high level of competence in digital security requires more theoretical and practical training. Future male Primary Education teachers, by contrast, perceive themselves as competent in digital security. This perhaps stems from their training (courses and workshops) in Information and Communication Technologies (ICT) and the theoretical and practical instruction they received at the university during courses or during a practicum. This aspect deserves further research because, as highlighted elsewhere, higher education institutions must prioritize instruction on digital security in their teacher programs.